2016
DOI: 10.7554/elife.19804
|View full text |Cite
|
Sign up to set email alerts
|

An essential cell-autonomous role for hepcidin in cardiac iron homeostasis

Abstract: Hepcidin is the master regulator of systemic iron homeostasis. Derived primarily from the liver, it inhibits the iron exporter ferroportin in the gut and spleen, the sites of iron absorption and recycling respectively. Recently, we demonstrated that ferroportin is also found in cardiomyocytes, and that its cardiac-specific deletion leads to fatal cardiac iron overload. Hepcidin is also expressed in cardiomyocytes, where its function remains unknown. To define the function of cardiomyocyte hepcidin, we generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
205
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(212 citation statements)
references
References 57 publications
5
205
0
2
Order By: Relevance
“…Thus, a local dysregulation of iron homeostasis in pulmonary vessels likewise contributes to the emergence of PAH, which, however, is not necessarily associated with systemic alterations of iron homeostasis. Interestingly, a similar mechanism of a locally regulated HAMP/FPN axis was found in cardiomyocytes, which may explain why dysregulation of iron homeostasis is also associated with poor clinical outcome in post-capillary PH patients with chronic heart disease [52].…”
Section: Interconnection Of Pulmonary Hypertension Iron Homeostasis mentioning
confidence: 74%
“…Thus, a local dysregulation of iron homeostasis in pulmonary vessels likewise contributes to the emergence of PAH, which, however, is not necessarily associated with systemic alterations of iron homeostasis. Interestingly, a similar mechanism of a locally regulated HAMP/FPN axis was found in cardiomyocytes, which may explain why dysregulation of iron homeostasis is also associated with poor clinical outcome in post-capillary PH patients with chronic heart disease [52].…”
Section: Interconnection Of Pulmonary Hypertension Iron Homeostasis mentioning
confidence: 74%
“…Notably, HAMP , a master regulator of iron homeostasis, was significantly enriched in over 50% of RA CM compared to 3% LA CM ( Supplementary Table B4 ) 29 , consistent with prior studies of RA tissues 8 and confirmed by smFISH ( Figure 2G ). HAMP has unknown roles in cardiac biology, but Hamp-null mice have electron transport chain deficits and lethal cardiomyopathy 30 . The RA enrichment of HAMP may imply energetic differences between right and left aCM.…”
Section: Prelid2mentioning
confidence: 99%
“…The production of hepcidin in these nonhepatocyte cell populations contributes insignificantly to systemic hepcidin levels and therefore systemic iron homeostasis, but recent reports suggest a local role for extrahepatic hepcidin in the autocrine and paracrine regulation of cellular iron. Despite normal systemic iron homeostasis and circulating hepcidin levels (99), the specific deletion of hepcidin in cardiomyocytes causes cardiac iron depletion and premature death, attributed to increased ferroportin expression in cardiomyocytes and excessive cellular iron efflux. Mice with global deletion of hepcidin may be protected from cardiac iron depletion by increased levels of circulating iron, including NTBI (81).…”
Section: Local Regulation Of Cellular Iron By Hepcidinmentioning
confidence: 99%